1992
DOI: 10.1002/ajh.2830400404
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of CD20 antigen as a characteristic marker for chronic lymphocytic leukemia

Abstract: The surface antigens expressed by the cells of chronic lymphocytic leukemia (CLL) are well known. Most CLL are monoclonal B-cell lymphoproliferative disorders characterized by the coexpression of B-cell antigens and CD5, an antigen present predominantly on T cells. Very little attention, however, has been paid to the quantitative characteristics of the expression of B-cell antigens in CLL. In this study, we used flow cytometry to analyze the expression of CD20, a well-known B-cell-associated antigen, in lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
94
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(105 citation statements)
references
References 15 publications
8
94
1
1
Order By: Relevance
“…At present, flow cytometry has been used to establish an immunophenotypic profile of B lymphocytes, that is characteristic of CLL, involving coexpression of CD5, CD19, CD20, and CD23 with low to absent expression of CD79b and FMC7. Low surface Ig expression and downregulation of CD20 are consistent finding in B-CLL (1)(2)(3)(4). However, the reported number of CD20 receptors per cell varies by more than 1 order of magnitude.…”
supporting
confidence: 58%
“…At present, flow cytometry has been used to establish an immunophenotypic profile of B lymphocytes, that is characteristic of CLL, involving coexpression of CD5, CD19, CD20, and CD23 with low to absent expression of CD79b and FMC7. Low surface Ig expression and downregulation of CD20 are consistent finding in B-CLL (1)(2)(3)(4). However, the reported number of CD20 receptors per cell varies by more than 1 order of magnitude.…”
supporting
confidence: 58%
“…The characteristic low intensity expression of CD20 in CLL is well established (26)(27)(28)(29). We also confirmed that the level of CD20 molecule numbers on CLL cells was low, being only 10% that of normal control B cells, as estimated by all standards tested.…”
Section: Discussionmentioning
confidence: 99%
“…However, extensive in vitro and preclinical studies suggest that Ab-dependent cell-mediated cytotoxicity (10,11), complement-dependent cytotoxicity (12)(13)(14)(15), and direct effects of transmembrane signaling leading to apoptosis and cell growth arrest (16 -18) may be responsible for the observed clinical effects of rituximab. Both in vitro and preclinical data suggest that decreased CD20 expression may be responsible for the lack of response observed in certain patients (12,19,20).…”
mentioning
confidence: 99%